2005
DOI: 10.1007/s00540-005-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flumazenil on recovery from sevoflurane anesthesia in children premedicated with oral midazolam before undergoing herniorrhaphy with or without caudal analgesia

Abstract: Caudal analgesia and avoiding the use of flumazenil synergistically resulted in the emergence from anesthesia in a less agitated state for children who underwent herniorrhaphy after oral midazolam premedication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…One new RCT corroborates findings reported in the original Guidelines regarding the efficacy of flumazenil to antagonize (i.e., reduced time to emergence) the residual effects of benzodiazepines after general anesthesia (Category A3-B evidence), 70 when compared with placebo. The original Guidelines also indicated that flumazenil reduces time to emergence after sedation (Category A1-B evidence); new literature is insufficient to further evaluate these findings.…”
Section: Antagonism Of the Effects Of Sedatives Analgesics And supporting
confidence: 72%
“…One new RCT corroborates findings reported in the original Guidelines regarding the efficacy of flumazenil to antagonize (i.e., reduced time to emergence) the residual effects of benzodiazepines after general anesthesia (Category A3-B evidence), 70 when compared with placebo. The original Guidelines also indicated that flumazenil reduces time to emergence after sedation (Category A1-B evidence); new literature is insufficient to further evaluate these findings.…”
Section: Antagonism Of the Effects Of Sedatives Analgesics And supporting
confidence: 72%
“…A recent CCT 79 Guidelines 17 claimed that flumazenil reduced the time to emergence following sedation (Evidence A1-B). Experts 17 disagree on the routine use of flumazenil to reduce the number of adverse events or improving patient comfort and satisfaction.…”
Section: Benzodiazepines Antagonistic Activitymentioning
confidence: 99%
“…Some studies have reported that midazolam which acts on its target effect site GABA A , reduces emergence agitation [5,6], and its antagonist, flumazenil reverses this effect [7]. However, the mechanism is still not clear, and it is not known whether sevoflurane and midazolam interact at the GABA A receptor level.…”
mentioning
confidence: 99%